Long‐term outcomes of endoscopic balloon dilation for intestinal strictures in patients with Crohn's disease during maintenance treatment with anti‐tumor necrosis factor alpha antibodies. Issue 3 (18th July 2021) - Takeda, Teruyuki; Kishi, Masahiro; Takatsu, Noritaka; Takada, Yasumichi; Beppu, Tsuyoshi; Miyaoka, Masaki; Hisabe, Takashi; Ueki, Toshiharu; Arima, Hisatomi; Hirai, Fumihito; Yao, Kenshi
Abstract : Background and aims: Efficacy of endoscopic balloon dilation (EBD) for intestinal strictures in patients with Crohn's disease (CD) receiving anti‐tumor necrosis factor alpha antibodies (anti‐TNF) as maintenance therapy is unclear. We investigated the long‐term efficacy and safety of EBD for intestinal strictures in patients with CD receiving anti‐TNF. Methods: We retrospectively analyzed data from patients with CD who received anti‐TNF as maintenance therapy from 2008 to 2017, underwent EBD, and were followed up for ≥6 months. The primary endpoint was the cumulative surgery‐free rate. The main secondary endpoints were technical success, repeat EBD rate, risk factors affecting surgical outcomes, and safety. Results: Seventy‐two patients with CD were assessed. The median observation period after EBD was 50 months. The technical success rate was 67%. The 3‐ and 5‐year cumulative surgery‐free rates were 81.1% and 73.5%, respectively. The repeat EBD rate was 74%. Multivariable analyses showed that risk factors affecting surgical outcomes were age at disease onset ≤16 years (hazard ratio 3.69; 95% confidence interval 1.36–10.01; P  = 0.011). Serious complications requiring surgery developed in three patients. Conclusions: Endoscopic balloon dilation was an effective and safe short‐term treatment and a useful long‐term treatment for CD patients with intestinal strictures receiving anti‐TNF as maintenance therapy.